A fully quantitative treatment process for landfill leachate
Through the four-stage continuous catalytic reaction process and the use of modified catalytic fillers, the problems of high contaminant concentration and high treatment cost in waste leachate treatment are solved, effective decomposition and degradation of organic matter and ammonia nitrogen are achieved, and treatment effect and safety are improved. sex.
Patent Information
- Application Number
- CN202410846081.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-27
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-06-27
AI Technical Summary
In the existing waste leachate treatment process, the membrane concentrate has high concentration of pollutants and poor biochemical properties, resulting in reduced membrane flux, increased material consumption and high treatment costs, and the catalytic wet oxidation and evaporation processes are immature and unstable in operation. .
Using the four-stage continuous catalytic reaction process, the full quantization treatment system of the regulation tank, multi-stage catalytic tank, slag separation system and clean water tank is used to utilize the alkaline and acidic reactions of the first-stage to four-stage catalytic tank, combined with the ozone generator and Fans use modified catalytic fillers to decompose organic matter and ammonia nitrogen to form sludge or carbon dioxide and nitrogen release.
Effectively decompose organic matter and ammonia nitrogen in the garbage leachate, significantly degrade difficult pollutants, improve the treatment effect of sewage, reduce treatment costs, and avoid secondary pollution.
Smart Images

Figure CN118702334B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of landfill leachate treatment technology and relates to a fully quantitative landfill leachate treatment technology. Background Art
[0002] Leachate refers to the wastewater formed by the water contained in the garbage itself in the landfill, the rain and snow water and other water entering the landfill, minus the saturated water holding capacity of the garbage and the covering soil layer, and passing through the garbage layer and the covering soil layer. Nowadays, most landfills and incineration plants in China use a combination of "biological method + membrane separation technology" to treat leachate, but they still face the big problem of membrane concentrate treatment. The concentrated liquid of the garbage leachate nanofiltration membrane filtration has complex components, high pollutant concentration, poor biodegradability, and it is easy to cause secondary pollution when it is re-injected into the landfill. With the increase in the number of times the concentrate is re-injected into the landfill, the concentration of persistent organic pollutants, heavy metals and salts in the leachate is getting higher and higher, resulting in a smaller membrane flux of the membrane treatment process, an increase in membrane material consumption, and an increasing treatment cost, which puts great pressure on the current leachate treatment process, and even causes the treatment process to be paralyzed and no water can be produced. The catalytic wet oxidation process and evaporation process currently available on the market are immature, unstable in operation or have a series of other problems. Summary of the invention
[0003] The purpose of the present invention is to provide a fully quantitative treatment process for landfill leachate. The present invention fully decomposes organic matter, ammonia nitrogen, etc. in the landfill leachate under the action of four-stage continuous catalytic reaction and releases them in the form of sludge or carbon dioxide, nitrogen, etc.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A full-quantity treatment process for landfill leachate is completed by a full-quantity treatment system, wherein the full-quantity treatment system comprises a regulating tank, a multi-stage catalytic tank, an intermediate water tank, a water-slag separation system and a clear water tank connected in sequence; the multi-stage catalytic tank comprises a primary alkaline catalytic tank, a secondary acidic catalytic tank, a tertiary alkaline catalytic tank and a quaternary three-way catalytic tank connected in sequence;
[0006] The full-scale treatment process of landfill leachate comprises the following steps:
[0007] Step 1: After the pH value of the landfill leachate is adjusted in the regulating tank, liquid A is obtained;
[0008] Step 2: Liquid A is transported to a multi-stage catalytic tank for treatment and the pH value is adjusted to obtain Liquid B;
[0009] Step 3: Liquid B is transported to the intermediate water tank, and after adjusting the pH, it is processed through the water-slag separation system and the clear water tank, and the treatment is completed.
[0010] As a preferred technical solution of the present invention, the regulating tank adjusts the pH to be greater than 9; the water-slag separation system functions to separate solid and liquid; the clear water tank functions to detect the waste liquid separated from the water-slag separation system and discharge it after it passes the test.
[0011] As a preferred technical solution of the present invention, the primary alkaline catalytic pool is provided with a primary ozone generator, the working parameters of the primary ozone generator are power 1.2KW / ton water, ozone amount 3-5mg / L water, reaction residence time 0.5-2 hours, and the pH value is adjusted to be less than 6 after treatment by the primary alkaline catalytic pool.
[0012] As a preferred technical solution of the present invention, the secondary acid catalytic pool is provided with a secondary fan, the working parameters of which are power 0.8KW / ton water, air volume 4-6m 3 / H, the reaction residence time is 0.5-2 hours, and the pH value is adjusted to be greater than 9 after being treated in the secondary alkaline catalytic tank.
[0013] As a preferred technical solution of the present invention, the three-stage alkaline catalytic pool is provided with a three-stage ozone generator, the working parameters of the three-stage ozone generator are power 1.2KW / ton water, ozone amount 3-5mg / L water, reaction residence time 0.5-2 hours, and the pH value is adjusted to be less than 6 after treatment in the first-stage alkaline catalytic pool.
[0014] As a preferred technical solution of the present invention, the four-stage three-way catalytic pool is provided with a four-stage fan, a four-stage ozone generator and a graphite electrode. The working parameters of the four-stage fan are power 0.8KW / ton of water, air volume 4-6m 3 / H, reaction residence time 0.5-2 hours; the working parameters of the four-stage ozone generator are power 1.2KW / ton water, ozone amount 3-5mg / L water, and reaction residence time 0.5-2 hours.
[0015] As a preferred technical solution of the present invention, the primary alkaline catalytic pool, the secondary acidic catalytic pool and the tertiary alkaline catalytic pool are all filled with catalytic fillers; the fourth-stage three-way catalytic pool is filled with modified catalytic fillers obtained by organically modifying the catalytic fillers.
[0016] As a preferred technical solution of the present invention, the preparation method of the modified catalytic filler comprises the following steps:
[0017] Step S1: placing the catalytic filler, ethanol and coupling agent in a reaction kettle, heating and stirring, adding chitosan solution and ultrasonically mixing, adding EDC and mercaptosuccinic acid and stirring and mixing in the dark, centrifuging and washing the solid, placing in an oven for vacuum drying, and obtaining a preform;
[0018] Step S2: After the preform and ethanol are placed in a reaction kettle and mixed evenly, phloroglucinol dialdehyde is added under an inert atmosphere, the mixture is heated and stirred, and then the solid is taken out by centrifugation for washing and placed in an oven for vacuum drying to obtain a modified catalytic filler.
[0019] As a preferred technical solution of the present invention, in step S1, the heating and stirring is stirring and mixing at a temperature of 50-60°C for 3-4 hours; the ultrasonic mixing is ultrasonic mixing at a frequency of 300-400W for 9-12 minutes; the stirring and mixing is stirring and mixing at a speed of 300-400r / min for 15-20 hours; the washing is washing with alcohol; the mass ratio of the catalytic filler, ethanol, coupling agent, chitosan solution, EDC and mercaptosuccinic acid is 30-36:100-120:3-4:14-20:0.7-0.8:0.50-0.62; the coupling agent is an amino-containing coupling agent selected from one or two of KH550 and KH560; the ethanol is anhydrous ethanol; the chitosan solution is a mixture of chitosan and deionized water at a ratio of 1:1000; and the vacuum drying is drying at a temperature of 80°C to constant weight.
[0020] As a preferred technical solution of the present invention, in step S2, the mixing time is 10-15 minutes; the inert atmosphere is a nitrogen atmosphere; the heating and stirring is heating to 60-68°C and stirring for 5-6 hours; the washing is washing with alcohol; the vacuum drying is dried at 85°C to constant weight; the mass ratio of the preform, ethanol and phloroglucinol dialdehyde is 18:60-70:0.25-0.28.
[0021] As a preferred technical solution of the present invention, the preparation method of the catalytic filler comprises the following steps:
[0022] Add carbon powder, manganese oxide, ferric oxide, sodium percarbonate, copper oxide, germanium oxide, zirconium oxide, aluminum oxide and sodium silicate into the ball mill one by one in order for ball milling. The ball milling process needs to last for 3-4 hours until a uniform ball mill material is obtained. Subsequently, the ball mill material is mixed with deionized water in a ratio of 1g:8-12mL and kneaded to form a kneaded material. After kneading, the kneaded material needs to be temperature-controlled and dried. The drying temperature is set at 110-120 ℃, and continue for 6-8 hours. After drying, temperature-controlled sintering is carried out. The sintering temperature is controlled at 800-1100℃, and the sintering time is 4-5 hours. Finally, after sintering is completed, the product is cooled, crushed, sieved, etc. to obtain catalytic filler; wherein the mass ratio of carbon powder, sodium percarbonate, copper oxide, germanium oxide, zirconium oxide, ferric oxide, aluminum oxide, manganese oxide and sodium silicate is 55:8:18:2:4:30:30:11:8.
[0023] Beneficial effects of the present invention:
[0024] (1) Under the action of four-stage continuous catalytic reactions, organic matter, ammonia nitrogen, etc. in the landfill leachate (mainly from the residues and bacteria in the garbage, including low molecular weight fatty acids, medium molecular weight fulvic acid substances, high molecular weight carbohydrate substances and humus substances) are fully decomposed and released in the form of sludge or carbon dioxide, nitrogen, etc. In this process, non-chlorinated aromatic compounds such as naphthalene and phenanthrene that are difficult to biodegrade, chlorinated aromatic compounds, phosphate esters, phthalates, phenolic compounds and aniline compounds, heavy metals, etc. in the landfill leachate are also treated together.
[0025] (2) The present invention uses carbon powder as a substrate, combines copper oxide, germanium oxide and other oxides and sodium percarbonate to prepare a high-efficiency catalytic filler to form a metal ion composite material, introduces amino groups on the surface of the catalytic filler through a coupling agent, and while EDC activates the carboxyl group of mercaptosuccinic acid and forms a chemical bond with chitosan, it grafts pyroglucin dialdehyde through the amino group to increase active sites, adsorb organic pollutants, and facilitate the degradation of pollutants, significantly removing COD in wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a flow chart of the fully quantitative treatment process for landfill leachate. DETAILED DESCRIPTION
[0027] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0028] A full-quantity treatment process for landfill leachate is completed by a full-quantity treatment system, wherein the full-quantity treatment system comprises a regulating tank, a multi-stage catalytic tank, an intermediate water tank, a water-slag separation system and a clear water tank connected in sequence; the multi-stage catalytic tank comprises a primary alkaline catalytic tank, a secondary acidic catalytic tank, a tertiary alkaline catalytic tank and a quaternary three-way catalytic tank connected in sequence;
[0029] The full-scale treatment process of landfill leachate comprises the following steps:
[0030] Step 1: After the pH value of the landfill leachate is adjusted in the regulating tank, liquid A is obtained;
[0031] Step 2: Liquid A is transported to a multi-stage catalytic tank for treatment and the pH value is adjusted to obtain Liquid B;
[0032] Step 3: Liquid B is transported to the intermediate water tank, and after adjusting the pH, it is processed through the water-slag separation system and the clear water tank, and the treatment is completed;
[0033] Among them, the multi-stage catalytic pool includes a primary alkaline catalytic pool, a secondary acidic catalytic pool, a tertiary alkaline catalytic pool and a fourth three-way catalytic pool connected in sequence, the primary alkaline catalytic pool is connected to the regulating pool, and the fourth three-way catalytic pool is connected to the intermediate water pool.
[0034] The regulating tank adjusts the pH to be greater than 9; the water-slag separation system is used to separate solid and liquid; the clear water tank is used to detect the waste liquid separated from the water-slag separation system and discharge it after it passes the test.
[0035] The primary alkaline catalytic pool is provided with a primary ozone generator, the working parameters of which are power 1.2KW / ton water, ozone amount 3-5mg / L water, reaction residence time 0.5-2 hours, and the pH value is adjusted to be less than 6 after treatment in the primary alkaline catalytic pool.
[0036] The secondary acid catalytic pool is provided with a secondary fan, the working parameters of which are power 0.8KW / ton water, air volume 4-6m 3 / H, the reaction residence time is 0.5-2 hours, and the pH value is adjusted to be greater than 9 after being treated in the secondary alkaline catalytic tank.
[0037] The three-stage alkaline catalytic pool is provided with a three-stage ozone generator, and the working parameters of the three-stage ozone generator are power 1.2KW / ton water, ozone amount 3-5mg / L water, reaction residence time 0.5-2 hours, and the pH value is adjusted to be less than 6 after treatment in the first-stage alkaline catalytic pool.
[0038] The four-stage three-way catalytic pool is provided with a four-stage fan, a four-stage ozone generator and a graphite electrode. The working parameters of the four-stage fan are power 0.8KW / ton of water, air volume 4-6m 3 / H, reaction residence time 0.5-2 hours; the working parameters of the four-stage ozone generator are power 1.2KW / ton water, ozone volume 3-5mg / L water, reaction residence time 0.5-2 hours; the working parameters of the graphite electrode are input current density 6-8mA / cm 2 Under the dual excitation of electric current and air, the alkaline catalyst filler plays a catalytic oxidation role.
[0039] The first-stage alkaline catalytic pool, the second-stage acidic catalytic pool and the third-stage alkaline catalytic pool are all filled with catalytic fillers; the fourth-stage three-way catalytic pool is filled with modified catalytic fillers obtained by organically modifying the catalytic fillers.
[0040] Example 1
[0041] The preparation method of the modified catalytic filler comprises the following steps:
[0042] Step S1: placing catalytic filler, ethanol and KH550 coupling agent in a reaction kettle for heating and stirring, adding chitosan solution for ultrasonic mixing, adding EDC and mercaptosuccinic acid for stirring and mixing in the dark, centrifuging to take out solids for washing, placing in an oven for vacuum drying, and obtaining a preform; wherein the heating and stirring is stirring and mixing at a temperature of 50°C for 3 hours; the ultrasonic mixing is ultrasonic mixing at a frequency of 300W for 9 minutes; the stirring and mixing is stirring and mixing at a speed of 300r / min for 15 hours; the washing is washing with alcohol; the vacuum drying is drying at a temperature of 80°C to constant weight; the mass ratio of the catalytic filler, ethanol, KH550 coupling agent, chitosan solution, EDC and mercaptosuccinic acid is 30:100:3:14:0.7:0.50; and the ethanol is anhydrous ethanol.
[0043] Step S2: after the preform and ethanol are placed in a reactor and mixed evenly, under an inert atmosphere, phloroglucinol dialdehyde is added and heated and stirred, the solid is centrifuged for washing, and the solid is placed in an oven for vacuum drying to obtain a modified catalytic filler; wherein, the mixing time is 10 minutes; the inert atmosphere is a nitrogen atmosphere; the heating and stirring is heating to 60°C and stirring for 5 hours; the washing is washing with alcohol; the vacuum drying is dried at 85°C to constant weight; the mass ratio of the preform, ethanol and phloroglucinol dialdehyde is 18:60:0.25.
[0044] The preparation method of the catalytic filler comprises the following steps:
[0045] Carbon powder, manganese oxide, ferric oxide, sodium percarbonate, copper oxide, germanium oxide, zirconium oxide, aluminum oxide and sodium silicate are added to a ball mill one by one in order for ball milling. The ball milling process needs to last for 3 hours until a uniform ball mill material is obtained. Subsequently, the ball mill material is mixed evenly with deionized water in a ratio of 1g:8mL, and kneading operation is performed to form a kneaded material. After kneading, the kneaded material needs to be temperature-controlled and dried, and the drying temperature is set at 110°C and lasts for 6 hours. After drying, temperature-controlled sintering is performed again, and the sintering temperature is controlled at 800°C and the sintering time is 4 hours. Finally, after sintering is completed, the product is cooled, crushed, sieved and the like to obtain a catalytic filler; wherein the mass ratio of the carbon powder, sodium percarbonate, copper oxide, germanium oxide, zirconium oxide, ferric oxide, aluminum oxide, manganese oxide and sodium silicate is 55:8:18:2:4:30:30:11:8.
[0046] Example 2
[0047] The preparation method of the modified catalytic filler comprises the following steps:
[0048] Step S1: placing catalytic filler, ethanol and KH550 coupling agent in a reaction kettle for heating and stirring, adding chitosan solution for ultrasonic mixing, adding EDC and mercaptosuccinic acid for stirring and mixing in the dark, centrifuging to take solids for washing, placing in an oven for vacuum drying, and obtaining a preform; wherein, the heating and stirring is stirring and mixing at a temperature of 53° C. for 3.5 hours; the ultrasonic mixing is ultrasonic mixing at a frequency of 330 W for 10 minutes; the stirring and mixing is stirring and mixing at a speed of 330 r / min for 17 hours; the washing is washing with alcohol; the vacuum drying is drying at a temperature of 80° C. to constant weight; the mass ratio of the catalytic filler, ethanol, KH550 coupling agent, chitosan solution, EDC and mercaptosuccinic acid is 32:107:3.3:16:0.73:0.54; and the ethanol is anhydrous ethanol.
[0049] Step S2: after the preform and ethanol are placed in a reactor and mixed evenly, under an inert atmosphere, phloroglucinol dialdehyde is added and heated and stirred, the solid is centrifuged for washing, and the solid is placed in an oven for vacuum drying to obtain a modified catalytic filler; wherein, the mixing time is 12 minutes; the inert atmosphere is a nitrogen atmosphere; the heating and stirring is heating to 63°C and stirring for 5.5 hours; the washing is washing with alcohol; the vacuum drying is dried at 85°C to constant weight; the mass ratio of the preform, ethanol and phloroglucinol dialdehyde is 18:63:0.26.
[0050] The preparation method of the catalytic filler comprises the following steps:
[0051] Carbon powder, manganese oxide, ferric oxide, sodium percarbonate, copper oxide, germanium oxide, zirconium oxide, aluminum oxide and sodium silicate are added to a ball mill one by one in order for ball milling. The ball milling process needs to last for 3.3 hours until a uniform ball mill material is obtained. Subsequently, the ball mill material is mixed evenly with deionized water in a ratio of 1g:9mL, and kneading operation is performed to form a kneaded material. After kneading, the kneaded material needs to be temperature-controlled and dried, and the drying temperature is set at 113°C and lasts for 6.5 hours. After drying, temperature-controlled sintering is performed again, and the sintering temperature is controlled at 900°C, and the sintering time is 4.5 hours. Finally, after sintering is completed, the product is cooled, crushed, sieved, etc. to obtain a catalytic filler; wherein the mass ratio of the carbon powder, sodium percarbonate, copper oxide, germanium oxide, zirconium oxide, ferric oxide, aluminum oxide, manganese oxide and sodium silicate is 55:8:18:2:4:30:30:11:8.
[0052] Example 3
[0053] The preparation method of the modified catalytic filler comprises the following steps:
[0054] Step S1: placing catalytic filler, ethanol and KH550 coupling agent in a reaction kettle for heating and stirring, adding chitosan solution for ultrasonic mixing, adding EDC and mercaptosuccinic acid for stirring and mixing in the dark, centrifuging to take solids for washing, placing in an oven for vacuum drying, and obtaining a preform; wherein, the heating and stirring is stirring and mixing at a temperature of 57° C. for 3.5 hours; the ultrasonic mixing is ultrasonic mixing at a frequency of 360 W for 11 minutes; the stirring and mixing is stirring and mixing at a speed of 360 r / min for 18 hours; the washing is washing with alcohol; the vacuum drying is drying at a temperature of 80° C. to constant weight; the mass ratio of the catalytic filler, ethanol, KH550 coupling agent, chitosan solution, EDC and mercaptosuccinic acid is 34:113:3.7:18:0.77:0.58; and the ethanol is anhydrous ethanol.
[0055] Step S2: after the preform and ethanol are placed in a reactor and mixed evenly, under an inert atmosphere, phloroglucinol dialdehyde is added and heated and stirred, the solid is centrifuged for washing, and the solid is placed in an oven for vacuum drying to obtain a modified catalytic filler; wherein, the mixing time is 13 minutes; the inert atmosphere is a nitrogen atmosphere; the heating and stirring is heating to 65°C and stirring for 5.5 hours; the washing is washing with alcohol; the vacuum drying is dried at 85°C to constant weight; the mass ratio of the preform, ethanol and phloroglucinol dialdehyde is 18:67:0.27.
[0056] The preparation method of the catalytic filler comprises the following steps:
[0057] Carbon powder, manganese oxide, ferric oxide, sodium percarbonate, copper oxide, germanium oxide, zirconium oxide, aluminum oxide and sodium silicate are added to a ball mill one by one in order for ball milling. The ball milling process needs to last for 3.5 hours until a uniform ball mill material is obtained. Subsequently, the ball mill material is mixed evenly with deionized water in a ratio of 1g:11mL, and kneading operation is performed to form a kneaded material. After kneading, the kneaded material needs to be temperature-controlled and dried, and the drying temperature is set at 117°C and lasts for 7.5 hours. After drying, temperature-controlled sintering is performed again, and the sintering temperature is controlled at 1000°C, and the sintering time is 4.5 hours. Finally, after sintering is completed, the product is cooled, crushed, sieved, etc. to obtain a catalytic filler; wherein the mass ratio of the carbon powder, sodium percarbonate, copper oxide, germanium oxide, zirconium oxide, ferric oxide, aluminum oxide, manganese oxide and sodium silicate is 55:8:18:2:4:30:30:11:8.
[0058] Example 4
[0059] The preparation method of the modified catalytic filler comprises the following steps:
[0060] Step S1: placing catalytic filler, ethanol and KH550 coupling agent in a reaction kettle for heating and stirring, adding chitosan solution for ultrasonic mixing, adding EDC and mercaptosuccinic acid for stirring and mixing in the dark, centrifuging to take out solids for washing, placing in an oven for vacuum drying, and obtaining a preform; wherein the heating and stirring is stirring and mixing at a temperature of 60° C. for 4 hours; the ultrasonic mixing is ultrasonic mixing at a frequency of 400 W for 12 minutes; the stirring and mixing is stirring and mixing at a speed of 400 r / min for 20 hours; the washing is washing with alcohol; the vacuum drying is drying at a temperature of 80° C. to constant weight; the mass ratio of the catalytic filler, ethanol, KH550 coupling agent, chitosan solution, EDC and mercaptosuccinic acid is 36:120:4:20:0.8:0.62; and the ethanol is anhydrous ethanol.
[0061] Step S2: after the preform and ethanol are placed in a reactor and mixed evenly, under an inert atmosphere, phloroglucinol dialdehyde is added and heated and stirred, the solid is centrifuged for washing, and the solid is placed in an oven for vacuum drying to obtain a modified catalytic filler; wherein, the mixing time is 15 minutes; the inert atmosphere is a nitrogen atmosphere; the heating and stirring is heating to 68° C. and stirring for 6 hours; the washing is washing with alcohol; the vacuum drying is dried at 85° C. to constant weight; the mass ratio of the preform, ethanol and phloroglucinol dialdehyde is 18:70:0.28.
[0062] The preparation method of the catalytic filler comprises the following steps:
[0063] Carbon powder, manganese oxide, ferric oxide, sodium percarbonate, copper oxide, germanium oxide, zirconium oxide, aluminum oxide and sodium silicate are added to a ball mill one by one in order for ball milling. The ball milling process needs to last for 4 hours until a uniform ball mill material is obtained. Subsequently, the ball mill material is mixed evenly with deionized water in a ratio of 1g:12mL, and kneading operation is performed to form a kneaded material. After kneading, the kneaded material needs to be temperature-controlled and dried, and the drying temperature is set at 120°C and lasts for 8 hours. After drying, temperature-controlled sintering is performed again, and the sintering temperature is controlled at 1100°C and the sintering time is 5 hours. Finally, after sintering is completed, the product is cooled, crushed, sieved and the like to obtain a catalytic filler; wherein the mass ratio of the carbon powder, sodium percarbonate, copper oxide, germanium oxide, zirconium oxide, ferric oxide, aluminum oxide, manganese oxide and sodium silicate is 55:8:18:2:4:30:30:11:8.
[0064] Comparative Example 1
[0065] Compared with Example 3, the difference in Comparative Example 1 is that no coupling agent is used in step S1, and the other components, preparation steps and parameters are the same.
[0066] Comparative Example 2
[0067] Compared with Example 3, the difference in Comparative Example 2 is that chitosan is not used in step S1, and the other components, preparation steps and parameters are the same.
[0068] Comparative Example 3
[0069] Compared with Example 3, the difference of Comparative Example 3 is that mercaptosuccinic acid is not used in step S1, and the other components, preparation steps and parameters are the same.
[0070] Comparative Example 4
[0071] Compared with Example 3, the difference in Comparative Example 4 is that step S2 does not use phloroglucinol dialdehyde, and the other components, preparation steps and parameters are the same.
[0072] Comparative Example 5
[0073] Compared with Example 3, the difference in Comparative Example 4 is that phthalaldehyde is used instead of phloroglucinol dialdehyde in step S2, and the other components, preparation steps and parameters are the same.
[0074] COD removal experiment: wastewater with a COD of 600 mg / L was used, the pH of the wastewater was adjusted to 9.1, and introduced into the reaction tank. A modified catalytic filler (selected from Examples 1-4 and Comparative Examples 1-5) was added to the reaction tank at a dosage ratio of 1.1 mL: 1 g. At the same time, the graphite electrode was connected to a power supply and the ozone generator was turned on for aeration for 1.5 hours; the ozone concentration of the ozone generator was 1 mg / L; COD removal rate: according to standard GB 11914-89, the results are shown in Table 1.
[0075] COD removal rate (%) = (COD 0 -COD 1 ) / COD 0 ×100%;
[0076] Where: COD 0 is the COD value of wastewater before treatment;
[0077] COD 1 is the COD value of the treated wastewater.
[0078] Table 1
[0079]
[0080]
[0081] From the test results in Table 1, it can be seen that compared with Comparative Examples 1-5, the modified catalytic filler prepared in Examples 1-4 has significantly better COD removal effect than Comparative Examples 1-5.
[0082] The invention uses carbon powder as a substrate, copper oxide, germanium oxide, zirconium oxide, manganese oxide, ferric oxide and sodium percarbonate to prepare a high-efficiency catalytic filler to form a metal ion composite material, then amino groups are introduced on the surface of the catalytic filler through a coupling agent, chitosan enters the pores of the catalytic filler, and the carboxyl groups of mercaptosuccinic acid are activated by EDC to form an amide bond connection between the amino groups and the carboxyl groups. While the thiol group is introduced, the amino group and phloroglucinol dialdehyde are used to form a Schiff base structure. The phloroglucinol dialdehyde has three hydroxyl structures, and the thiol, amide structure and Schiff base structure are combined to enrich the active sites of the prepared modified catalytic filler. Through diversified chemical adsorption, organic pollutants can be more effectively adsorbed to form an intermediate transition state, the catalyst activity is fully exerted, and it is more conducive to the degradation of organic pollutants, sufficient active sites are provided for subsequent ozone redox reaction, COD in wastewater can be significantly removed, chemical catalytic redox reaction is promoted through the dual effects of ozone and electric current, and the removal effect of COD is enhanced.
[0083] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A fully quantitative treatment process for landfill leachate, characterized in that: The full-quantity treatment process of the landfill leachate is completed by a full-quantity treatment system, which includes a regulating tank, a multi-stage catalytic tank, an intermediate water tank, a water-slag separation system and a clear water tank connected in sequence; the multi-stage catalytic tank includes a primary alkaline catalytic tank, a secondary acidic catalytic tank, a tertiary alkaline catalytic tank and a quaternary three-way catalytic tank connected in sequence; The full-scale treatment process of landfill leachate comprises the following steps: Step 1: After the pH value of the landfill leachate is adjusted in the regulating tank, liquid A is obtained; Step 2: Liquid A is transported to a multi-stage catalytic tank for treatment and the pH value is adjusted to obtain Liquid B; Step 3: Liquid B is transported to the intermediate water tank, and after adjusting the pH, it is processed through the water-slag separation system and the clear water tank, and the treatment is completed; Wherein, the primary alkaline catalytic pool is connected to the regulating pool, and the fourth-stage three-way catalytic pool is connected to the intermediate water pool; The first-stage alkaline catalytic pool, the second-stage acidic catalytic pool and the third-stage alkaline catalytic pool are all filled with catalytic fillers; the fourth-stage three-way catalytic pool is filled with modified catalytic fillers obtained by organically modifying the catalytic fillers; The preparation method of the catalytic filler comprises the following steps: Add carbon powder, manganese oxide, ferric oxide, sodium percarbonate, copper oxide, germanium oxide, zirconium oxide, aluminum oxide and sodium silicate into the ball mill one by one in order for ball milling. The ball milling process needs to last for 3-4 hours until a uniform ball mill material is obtained. Subsequently, the ball mill material is mixed with deionized water in a ratio of 1g:8-12mL and kneaded to form a kneaded material. After kneading, the kneaded material needs to be temperature-controlled and dried. The drying temperature is set at 110-12 0℃ and continue for 6-8 hours. After drying, temperature-controlled sintering is carried out. The sintering temperature is controlled at 800-1100℃ and the sintering time is 4-5 hours. Finally, after sintering, the product is cooled, crushed and sieved to obtain catalytic filler. The mass ratio of carbon powder, sodium percarbonate, copper oxide, germanium oxide, zirconium oxide, iron oxide, aluminum oxide, manganese oxide and sodium silicate is 55:8:18:2:4:30:30:11:
8.
2. The method for fully quantifying landfill leachate according to claim 1 is characterized in that: The regulating tank adjusts the pH to be greater than 9; the water-slag separation system is used to separate solid and liquid; the clear water tank is used to detect the waste liquid separated from the water-slag separation system and discharge it after it passes the test.
3. The method for fully quantifying landfill leachate according to claim 1 is characterized in that: The primary alkaline catalytic pool is provided with a primary ozone generator, the working parameters of which are power 1.2KW / ton water, ozone amount 3-5mg / L water, reaction residence time 0.5-2 hours, and the pH value is adjusted to be less than 6 after treatment in the primary alkaline catalytic pool.
4. The method for fully quantifying landfill leachate according to claim 1 is characterized in that: The secondary acid catalytic pool is provided with a secondary fan, the working parameters of the secondary fan are power 0.8KW / ton of water, air volume 4-6m³ / h, reaction residence time 0.5-2 hours, and the pH value is adjusted to be greater than 9 after treatment in the secondary acid catalytic pool.
5. The full-scale treatment process for landfill leachate according to claim 1 is characterized by: The three-stage alkaline catalytic pool is provided with a three-stage ozone generator, and the working parameters of the three-stage ozone generator are power 1.2KW / ton water, ozone amount 3-5mg / L water, reaction residence time 0.5-2 hours, and the pH value is adjusted to be less than 6 after treatment in the first-stage alkaline catalytic pool.
6. The full-scale treatment process for landfill leachate according to claim 1 is characterized by: The four-stage three-way catalytic pool is provided with a four-stage fan, a four-stage ozone generator and a graphite electrode. The working parameters of the four-stage fan are power 0.8KW / ton of water, air volume 4-6m³ / h, and reaction residence time 0.5-2 hours; the working parameters of the four-stage ozone generator are power 1.2KW / ton of water, ozone volume 3-5mg / L of water, and reaction residence time 0.5-2 hours.
